Comparing the cost of dental services during Covid-19 pandemic and earlier by activity-based costing - Yasaman Azimi; Zahra Ghorbani; Tayebe Rojhanian (Tehran University of Medical Sciences, 2022)
Background and Aims: Activity-based costing enumerate every input consumed in treatment. The Covid-19 pandemic changed the dental treatment protocols and the ordinary circumstances of patients. The aim of this study was to calculate and compare the costs of three common dental services in Iran from the viewpoint of the providers and recipients of the services before the Covid-19 pandemic (2019) and during the pandemic (2021). Materials and Methods: Direct medical and non-medical costs were considered from the service provider's perspective. Direct medical costs, indirect costs, direct non-medical costs, and intangible costs were considered from the recipient's perspective. To calculate the equivalent costs, the base year was considered 2021, and the costs of 2019 were calculated with a discount rate of 16%. Results: From the service provider's perspective before the pandemic, the cost of dental amalgam restoration was 2,851,235 Rials, root canal treatment was 6,351,580 Rials, and tooth extraction was 1,887,295 Rials. The cost of these services in 2021 was 5,562,150 Rials, 8,070,591 Rials, and 4,865,563 Rials, respectively. From the recipient's perspective, before the pandemic, the cost of tooth restoration was 715,466 Rials, root canal treatment was 2,883,001 Rials, and tooth extraction was 3,267,359 Rials. The cost of the mentioned services in the year 2021 was 1,212,528 Rials, 3,971,640, and 3,680,880 Rials, respectively. Conclusion: The Covid-19 pandemic has had an effect on increasing the cost of dental services from both the service provider and recipient perspective, but economic volatility has a vital role in increasing the estimated costs in the country. Probably, a part of the increase in costs was due to the role of brokers in providing dental materials and equipment.